Clonal diversity of Acinetobacter baumannii clinical isolates in Myanmar: identification of novel ST1407 harbouring blaNDM-1 - Aung, M.S. (New Microbes New Infect, 2021)
Recent Acinetobacter baumannii clinical isolates in a teaching hospital in Myanmar comprised three major sequence types (ST2, ST16 and ST23) and two sporadic STs, showing a high resistance rate to carbapenem associated with bla(OXA-23). The NDM-1 encoding gene was identified in only one isolate exhibiting novel ST1407 (a triple-locus variant of ST16).